Gene and Cell Therapy for Epilepsy: A Mini Review - Shaimardanova, Alisa A.; Chulpanova, Daria S.; Mullagulova, Aysilu I.; Afawi, Zaid; Gamirova, Rimma G.; Solovyeva, Valeriya V.; Rizvanov, Albert A. (Frontiers in Molecular Neuroscience, 2022)
Epilepsy is a chronic non-infectious disease of the brain, characterized primarily by recurrent unprovoked seizures, defined as an episode of disturbance of motor, sensory, autonomic, or mental functions resulting from excessive neuronal discharge. Despite the advances in the treatment achieved with the use of antiepileptic drugs and other non-pharmacological therapies, about 30% of patients suffer from uncontrolled seizures. This review summarizes the currently available methods of gene and cell therapy for epilepsy and discusses the development of these approaches. Currently, gene therapy for epilepsy is predominantly adeno-associated virus (AAV)-mediated delivery of genes encoding neuro-modulatory peptides, neurotrophic factors, enzymes, and potassium channels. Cell therapy for epilepsy is represented by the transplantation of several types of cells such as mesenchymal stem cells (MSCs), bone marrow mononuclear cells, neural stem cells, and MSC-derived exosomes. Another approach is encapsulated cell biodelivery, which is the transplantation of genetically modified cells placed in capsules and secreting various therapeutic agents. The use of gene and cell therapy approaches can significantly improve the condition of patient with epilepsy. Therefore, preclinical, and clinical studies have been actively conducted in recent years to prove the benefits and safety of these strategies.